Prevention of eating disorders at universities: A systematic review and meta-analysis - Harrer, Mathias; Adam, Sophia H.; Messner, Eva-Maria; Baumeister, Harald; Cuijpers, Pim; Bruffaerts, Ronny; Auerbach, Randy P.; Kessler, Ronald C.; Jacobi, Corinna; Taylor, Craig Barr; Ebert, David D. (International Journal of Eating Disorders, 2020)
Background Eating problems are highly prevalent among young adults. Universities could be an optimal setting to prevent the onset of eating disorders through psychological intervention. As part of the World Mental Health-International College Student initiative, this systematic review and meta-analysis synthesizes data on the efficacy of eating disorder prevention programs targeting university students. Method A systematic literature search of bibliographical databases (CENTRAL, MEDLINE, PsycINFO) for randomized trials comparing psychological preventive interventions for eating disorders targeting university students with psychoeducation or inactive controls was performed on October 22, 2019. Results Twenty-seven studies were included. Thirteen (48.1%) were rated to have a low risk of bias. The relative risk of developing a subthreshold or full-blown eating disorder was incidence rate ratio = 0.62 (95% CI [0.44, 0.87], n(c) = 8, numbers-needed-to-treat [NNT] = 26.08; standardized clinical interviews only), indicating a 38% decrease in incidence in the intervention groups compared to controls. Small to moderate between-group effects at posttest were found on eating disorder symptoms (g = 0.35, 95% CI [0.24, 0.46], NNT = 5.10, n(c) = 26), dieting (g = 0.43, 95% CI [0.29, 0.57], NNT = 4.17, n(c) = 21), body dissatisfaction (g = 0.40, 95% CI [0.27, 0.53], NNT = 4.48, n(c) = 25), drive for thinness (g = 0.43, 95% CI [0.27, 0.59], NNT = 4.23, n(c) = 12), weight concerns (g = 0.33, 95% CI [0.10, 0.57], NNT = 5.35, n(c) = 13), and affective symptoms (g = 0.27, 95% CI [0.15, 0.38], NNT = 6.70, n(c) = 18). The effects on bulimia nervosa symptoms were not significant. Heterogeneity was moderate across comparisons. Discussion Eating disorder prevention on campus can have significant, small-to-moderate effects on eating disorder symptoms and risk factors. Results also suggest that the prevention of subthreshold and full-syndrome eating disorders is feasible using such interventions. More research is needed to identify ways to motivate students to use preventive eating disorder interventions. Antecedentes Los trastornos de la conducta alimentaria son altamente prevalentes entre los adultos jovenes. Las universidades podrian ser un entorno optimo para prevenir la aparicion de trastornos alimentarios a traves de la intervencion psicologica. Como parte de la iniciativa World Mental Health-International College Student, esta revision sistematica y meta-analisis sintetiza datos sobre la eficacia de los programas de prevencion de trastornos alimentarios dirigidos a estudiantes universitarios. Metodo Una busqueda bibliografica sistematica de datos bibliograficas (CENTRAL, MEDLINE, PsycINFO) para ensayos aleatorios que comparaban intervenciones preventivas psicologicas para trastornos alimentarios dirigidos a estudiantes universitarios con psicoeducacion o controles inactivos fue realizada hasta el 22 de octubre de 2019. Resultados Se incluyeron 27 estudios. Trece (48,1%) fueron calificados como de bajo riesgo de sesgo. El riesgo relativo de desarrollar un trastorno de la conducta alimentaria subclinico (parcial) o completo fue IRR = 0.62 (95% CI [0.44, 0.87], n(c) = 8, NNT = 26.
CRIS-Team WoS Importer:2020-01-24